Shoot iron status and auxin are involved in iron deficiency-induced phytosiderophores release in wheat - Garnica, Maria (2018)
Background: The release of phytosiderephores (PS) to the rhizosphere is the main root response to iron (Fe) deficiency in graminaceous plants. We have investigated the role of the Fe status in the shoot as well as of the signaling pathways controlled by three relevant phytoregulators - indolacetic acid (IAA), ethylene and nitric oxide (NO) - in the regulation of this root response in Fe-starved wheat plants. To this end, the PS accumulation in the nutrient solution and the root expression of the genes encoding the nicotianamine aminotransferase (TaNAAT) and ferritin (TaFER) have been evaluated in plants subjected to different treatments. Results: The application of Fe to leaves of Fe-deficient plants prevented the increase in both PS root release and TaNAAT gene expression thus showing the relevant role of the shoot to root communication in the regulation of PS root release and some steps of PS biosynthesis. Experiments with specific hormone inhibitors showed that while ethylene and NO did not positively regulate Fe-deficiency induced PS root release, auxin plays an essential role in the regulation of this process. Moreover, the application of IAA to Fe-sufficient plants promoted both PS root release and TaNAAT gene expression thus indicating that auxin might be involved in the shoot to root signaling network regulating Fe-deficiency root responses in wheat. Conclusions: These results therefore indicate that PS root release in Fe-deficient wheat plants is directly modulated by the shoot Fe status through signaling pathways involving, among other possible effectors, auxin.